2008
DOI: 10.1038/msb.2008.63
|View full text |Cite
|
Sign up to set email alerts
|

The temporal response of the Mycobacterium tuberculosis gene regulatory network during growth arrest

Abstract: The virulence of Mycobacterium tuberculosis depends on the ability of the bacilli to switch between replicative (growth) and non-replicative (dormancy) states in response to host immunity. However, the gene regulatory events associated with transition to dormancy are largely unknown. To address this question, we have assembled the largest M. tuberculosis transcriptional-regulatory network to date, and characterized the temporal response of this network during adaptation to stationary phase and hypoxia, using p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
148
0
1

Year Published

2009
2009
2019
2019

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 116 publications
(153 citation statements)
references
References 48 publications
(65 reference statements)
4
148
0
1
Order By: Relevance
“…Our result is in sharp contrast with what would arise in a model without molecular modeling of the interactions. Sparseness would then have to be enforced in an ad-hoc way because biological networks are indeed sparse experimentally (41,42).…”
Section: Resultsmentioning
confidence: 99%
“…Our result is in sharp contrast with what would arise in a model without molecular modeling of the interactions. Sparseness would then have to be enforced in an ad-hoc way because biological networks are indeed sparse experimentally (41,42).…”
Section: Resultsmentioning
confidence: 99%
“…It has been shown that distinct topological units (called origons) at the root of these hierarchies are significantly affected by environmental signals (8). These origons have been shown to be responsive at various stages of adaptation of Mycobacterium tuberculosis allowing a gradual progression of network under both replicative (growth) and nonreplicative (dormancy) states (9). Evolutionary analysis of Escherichia coli showed that transcriptional networks tend to grow by expansion of existing hierarchical layers, rather than addition of new layers (10).…”
mentioning
confidence: 99%
“…Understanding the environmental cues that are important during infection, and the regulatory cascades that are triggered, will precipitate novel intervention strategies for combating M.tuberculosis disease. A major benefit of these global profiling datasets is the ability to attribute predicted action to genes of unknown function using gene regulatory or protein network modelling [24,50]. Such interaction networks, together with metabolic models of M.tb [51], will be required to map and digest the huge quantity of mRNA abundance data generated from microarray and sequencing projects.…”
Section: Regulation Of Gene Expressionmentioning
confidence: 99%